74.6k views
2 votes
Z - 3( z + 2 ) = -6 - 2z

2 Answers

5 votes

Answer:

0

Explanation:

just multiply and bring the numbers to the other sides and both equal 0

User BirgerH
by
5.2k points
2 votes

Answer: depends (read explanation)

Either 0=0 (doubt) or:

Z= -3

Explanation:

1.Assuming that whole line is the equation:

Group like terms. Put all z terms on one side and normal numbers on the other.

There are brackets so remove them first.

Z-3z-6=-6-2z

-2z+2z=-6+6

0=0

2. If you started the question already and got to -6-2z=0:

-6=2z

Z=-6/2

Z=-3

User Skoua
by
4.7k points